Families dealing with the uncertainty of genetic disorders: the case of Neurofibromatosis Type 1. Issue 5 (11th February 2016) - Carrieri, Daniele; Farrimond, Hannah; Kelly, Susan; Turnpenny, Peter
Abstract: Some scholars contend that genetic medicine is transforming the experience of illness and the social category of the family – bringing future risks into the present, and potentially strengthening familial biological bonds in light of these shared genetic risks. However, research has shown that genetic information is interpreted and acted upon through a rich repertoire of adaptable social, cultural and familial factors which pre‐exist and interact with biomedical knowledge. This paper reports research into families living with Neurofibromatosis Type 1 (NF1), a highly uncertain condition the manifestation of which can vary considerably also within the same family and, for this reason, has been defined as a 'condition without parameters'. These characteristics make NF1 a particularly informative condition for the examination of family dynamics around genetic information. The study and the methodology are based on the exploration of family networks and allow us to investigate the interrelation of individual and familial constructions of the uncertainty of NF1. This also allows both theoretical and policy claims to be made about the danger of reductionist thinking about the transformative potential of genetic technologies.